Lexical Devices in Political Speech (A Study on Gorontalo Mayoral Election 2018) - Sri Widyarti Ali (Jambura Journal of English Teaching and Literature, 2020)
The use of language in political campaign speech is always interesting to be observed. It mostly contains language features which are intended to convince or persuade people to vote someone into power. Therefore, the language used in political speech has always attracted linguist’ attention to conduct the study of political discourse. This study is aimed to identify and analyze the lexical devices in political campaign speech delivered by the politicians in Gorontalo mayoral election 2018. The data of the lexical cohesive devices are analyzed based on the theory of lexical cohesion proposed by Halliday and Hasan in 1976. Halliday and Hasan have divided the lexical cohesion into two types; reiteration and collocation. Furthermore, the reiteration has four sub-types; repetition, synonym/near synonym, superordinate, and general word. The data identification reveals that the reiteration and the collocation are both found in the speeches. They are successfully used as the tools to deliver the speakers purposes and intentions. Hopefully, this study gives more knowledge and insight to others, especially to the language learners, about how the lexical devices are used in political speeches, and more importantly about how language plays its roles to make people get convinced and persuaded.